Efficacy of the maxillary anterior segmental distraction osteogenesis in patients with cleft lip and palate - Panjun Pu; Shanying Bao; Jianbo Gao; Yuhua Jiao; Feiyu Wang; Huaxiang Zhao; Yuxia Hou; Yalin Zhan (BMC, 2024)
Abstract Background Cleft lip and palate (CLP) is one of the most common birth defects worldwide. It typically results in significant maxillary dysplasia, causing severe oral function problems and substantially affecting the patient's facial aesthetics. Maxillary anterior segmental distraction osteogenesis (MASDO) has gained popularity in recent years as an effective treatment for correcting maxillary dysplasia. However, the evaluation of its effectiveness in patients with CLP varies across different studies. Our research was aimed at providing evidence of the effects of MASDO among CLP patients. Methods A meta-analysis covered Medline, Web of Science, Embase, Scopus, and Cochrane Library. Controlled clinical trial studies published before February 2024 and analyzed changes in maxillary cephalometric landmarks before and after MASDO among patients with maxillary hypoplasia and CLP were included. Results Our meta-analysis included 10 papers in total. One study was at low risk of bias, seven were at medium risk, and two were at serious risk. MASDO significantly increased the maxillary length. The mean SNA angle increased by 6.43° (95% CI, 4.11° to 8.74°) and A-McNamara rose by 7.29 mm (95% CI, 6.21 mm to 8.37 mm). The maxilla also showed a slight counterclockwise rotation; however, this reached no statistical significance. The mandibular position did not vary remarkably. Moreover, a significant increase in upper anterior tooth tipping and overjet, a decrease in overbite, and an improvement in nasolabial soft tissue were observed. Conclusions MASDO might be a valid therapy option for CLP patients. It causes a significant increase in the maxillary length, anterior tooth crossbite, and nasolabial soft tissue were also greatly improved.